Les relations sociales des jeunes face aux discours d’activation des politiques de la jeunesse : analyse croisée des parcours atypiques de jeunes adultes vulnérables sur trois terrains de recherche au Québec - Jonathan Binet; Sara Lambert; Marc Molgat (Sociétés et Jeunesses en Difficulté)
This article questions the activation discourses of Quebec discourses with the concrete relational realities of vulnerable young adults whose policies relating to youth by juxtaposing the intentions presented in these paths are atypical in relation to housing, education and work. It poses the hypothesis that the official discourses of Quebec activation policies and their intention to accelerate transitions to adult life convey concepts that are likely to generate normative tensions among young adults by demanding that they become quickly independent and engage in active life, with very little regard for the conditions and relational supports to which they have access. It first analyzes the discourses of three Quebec policies which, although they are aimed at different groups of young people, renew injunctions for activation encouraging them to quickly adopt independent lifestyles. It then describes the social relationships of vulnerable young adults with atypical backgrounds which deviate, at different levels, from the norms relating to schooling, employment, and housing, drawing on results from three research projects that took place in the Outaouais region, Quebec. By juxtaposing the study of the discourses of these three Quebec policies with the analysis of the relationships of young adults, the article questions the use of the concepts of autonomy, stabilization, and life project for the purposes of activation and the acceleration of transitions to adult life.